Retrospective analysis of sex-disaggregated immune responses to ALVAC-HIV and bivalent subtype C gp120/MF59 HIV vaccines - Ackerley, Cassie G.; Edupuganti, Srilatha; Yu, Chenchen; Roxby, Alison C.; Seaton, Kelly E.; Bekker, Linda-Gail; Allen, Mary; DeRosa, Stephen C.; Yates, Nicole L.; Heptinstall, Jack; Mkhize, Nonhlanhla N.; Malahleha, Mookho; et al. (Frontiers in Immunology, 2025)
IntroductionGenerally, individuals assigned female at birth (AFAB) develop greater immunogenicity to various vaccines than individuals assigned male at birth (AMAB). Little is known about sex-disaggregated immunogenicity to HIV-1 vaccines. We disaggregated immune responses to an experimental HIV vaccine regimen.MethodsWe retrospectively analyzed data from HVTN 100, a clinical trial conducted in South Africa during which 143 adults AMAB and 109 AFAB aged 18–40 years without HIV received ALVAC-HIV vCP2438 plus bivalent subtype C gp120/MF59 or placebo at 0, 1, 3, 6, and 12 months. Eligible data were from per-protocol vaccine recipients at month 6.5. We measured IgG binding antibodies, neutralizing antibodies, antibody-dependent cell-mediated cytotoxicity (ADCC), antibody-dependent cellular phagocytosis (ADCP), and CD4+ IFNγ and/or II-2 responses. We compared sex-based differences in response rates using Barnard’s test and response magnitudes using Wilcoxon Rank Sum test. P-values were Holm-adjusted for multiple comparisons.ResultsOf 185 vaccine recipients, 73 were AFAB and 112 were AMAB. Vaccine recipients AFAB had greater ADCC response rate (57.5% versus 29.5%; padj = 0.0003) and greater ADCC magnitude (area under the net % granzyme B activity vs log10 curve (AUC), 16.1 versus 11.2; padj = 0.05) to vaccine-matched antigen TV1.C gp120 compared to AMAB. Vaccine recipients AMAB had higher CD4+ T cell response rates to 2/3 vaccine-matched antigens at month 6.5 (ZM96.C gp120, [54.1% versus 36.8%; padj = 0.04]; 1086.C gp120, [44.1% versus 29.4%; padj = 0.05]) than AFAB. CD4+ T cell response magnitudes were similar by sex. IgG binding antibody response rate to B.CaseA V1V2 antigen (associated with reduced HIV acquisition risk in the RV144 trial) was 56.8% among AMAB vaccine recipients versus 38.9% among AFAB (padj = 0.08). There were no sex-based differences in neutralizing antibody or ADCP responses.DiscussionWe identified sex-based differences in immune responses to an HIV vaccine regimen, but they varied by immunologic assay. While vaccine recipients AFAB demonstrated higher ADCC responses, AMAB exhibited higher CD4+ T cell response rates. Future analyses should investigate whether vaccine factors such as platform, dosing and adjuvants contribute to sex-based differences in immunogenicity of experimental HIV vaccines.